Anticancer effect of berberine based on experimental animal models of various cancers: a systematic review and meta-analysis - Xu, Jianhao; Long, Yuming; Ni, Liwei; Yuan, Xuya; Yu, Na; Wu, Runhong; Tao, Jialong; Zhang, Yusong (BMC cancer, 2019)
Background Numerous studies have explored the anti-tumor effect of berberine (BBR), but little clinical evidence guides the use of BBR in cancer patients. Objectives Our aim was to investigate the impact of BBR on various cancers in healthy animals to promote the transformation from bench to bed. Search methods PubMed, Embase, Springer, and Cochrane databases were searched from January 2000 to October 2018 for relevant articles. Selection criteria Only published studies focusing on the relationship between BBR and various cancers in vivo were qualified. Two review authors independently assessed the risk of bias for each study, and any disagreement was resolved by discussion or by involving a third assessor. Results A total of 26 studies from 2000 to 2018, focusing on various cancer types, including breast cancer, liver cancer, colorectal cancer, nasopharyngeal carcinoma, lung cancer, gastric cancer, neuroepithelial cancer, endometrial carcinoma, esophageal cancer, tongue cancer, cholangiocarcinoma, and sarcoma were included. Overall, BBR reduced tumor volume (SMD =3.72, 95% CI: 2.89, 4.56, Z = 8.73, p < 0.00001) and tumor weight (SMD =2.35, 95% CI: 1.51, 3.19, Z = 5.50, p < 0.00001) in a linear The dose–response relationship (Pearson r = − 0.6717, p < 0.0001 in tumor volume analysis; Pearson r = − 0.7704, p < 0.0005 in tumor weight analysis). BBR inhibited angiogenesis in tumor tissues (SMD = 4.29, 95% CI: 2.14, 6.44, Z = 3.92, p < 0.00001), but it had no significant effect on the body weight of experimental animals (SMD = 0.11, 95% CI: − 0.70, 0.92, Z = 0.27, p = 0.78). Publication bias was not detected. Conclusion BBR exerted anti-tumor effects in a variety of tumors in vivo, especially breast cancer and lung cancer, and the evidence was still insufficient in colorectal cancer and gastric cancer.